2020
DOI: 10.1186/s13287-019-1530-4
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles for acute kidney injury in preclinical rodent models: a meta-analysis

Abstract: IntroductionExtracellular vesicles (EVs), especially stem cell-derived EVs, have emerged as a potential novel therapy for acute kidney injury (AKI). However, their effects remain incompletely understood. Therefore, we performed this meta-analysis to systematically review the efficacy of EVs on AKI in preclinical rodent models.MethodsWe searched PubMed, EMBASE, and the Web of Science up to March 2019 to identify studies that reported the treatment effects of EVs in a rodent AKI model. The primary outcome was se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 59 publications
(110 reference statements)
2
29
0
1
Order By: Relevance
“…It is now widely accepted that MSC-exosomes are the next-generation of regenerative therapeutics capable of targeting multiple pathways with regenerative function and overcoming the limitations of cell-based therapeutics [14,53,54]. Several studies have already demonstrated the therapeutic effects of MSC-exosomes from different cell sources, including bone marrow, Wharton's Jelly, and umbilical cords, in a diversity of AKI animal models [7][8][9]. For instance, injection of human umbilical cord-MSC (UC-MSC)-derived exosomes reduced apoptosis and necrosis of proximal kidney tubules by ameliorating oxidative stress in a cisplatin-induced rat AKI model.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is now widely accepted that MSC-exosomes are the next-generation of regenerative therapeutics capable of targeting multiple pathways with regenerative function and overcoming the limitations of cell-based therapeutics [14,53,54]. Several studies have already demonstrated the therapeutic effects of MSC-exosomes from different cell sources, including bone marrow, Wharton's Jelly, and umbilical cords, in a diversity of AKI animal models [7][8][9]. For instance, injection of human umbilical cord-MSC (UC-MSC)-derived exosomes reduced apoptosis and necrosis of proximal kidney tubules by ameliorating oxidative stress in a cisplatin-induced rat AKI model.…”
Section: Discussionmentioning
confidence: 99%
“…As observed in other disease models, various miRNA cargoes, such as miR-30, miR-199a-5p, miR-486-5p in MSC-exosomes also contribute to the protective and renal-regenerative effects in AKI models as well [58][59][60]. However, the clinical translation of these studies is limited by available exosome-isolation methods; ultracentrifugation-based isolation methods were applied in all of the 31 reported studies on preclinical rodent models [9]. Ultracentrifugation is the most widely used method for isolating exosomes from the MSC-CM [61].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Preclinical studies reiterate the ability MSCs have on dampening lung inflammation. This capacity is largely due to the paracrine secretion of MSC factors (microvesicles, exosomes) that provide a basis for future cell-free therapies for human disease [28][29][30][31]. This is the first review to directly compare the effects of CdM vs MSCs on lung structure and function in animal models of diverse lung disease.…”
Section: Discussionmentioning
confidence: 99%